PELATIHAN MICROSOFT OFFICE POINT SECARA DARING DALAM MENINGKATKAN MOTIVASI BELAJAR PADA ANAK JALANAN CAHAYA ANAK NEGERI - Melyani Melyani (Lembaga Penelitian dan Pengabdian kepada Masyarakat UIKA Bogor, 2024)
Community Service Our group collaborates with the Jalan Children's Partner Cahaya Anak Negeri which is located at Jl, KP Pintu Air No 55 RT 002 RW 007 Kel. Harapan Mulya, District. Medan Satria, Bekasi City. West Java 17143. Cahaya Anak Negri is a small studio located behind Bekasi station. This studio is a home for street children, orphans, and poor people who want to learn and play with their friends. The theme of community service given by the children of Jalan Cahaya Anak Negeri is entitled Online Microsoft Office PowerPoint Training in Improving Learning for the Children of Jalan Cahaya Anak Negeri. By providing knowledge to the children of Jalan Cahaya Anak Negeri, they will gain new knowledge, for motivate for them to be enthusiastic about learning, by providing training on the use of PowerPoint in learning. They can use PowerPoint in their daily activities in doing school assignments. The target output is in the form of articles in print or electronic media, activity videos as a form of activity documentation, and increasing knowledge from partners. The implementation method for this activity consists of the preparation stage, namely surveying the activity location, the implementation stage, training in PowerPoint as an online use of information technology, training in using PowerPoint in learning, training in using the PowerPoint application for learning activities related to writing, columns, pictures, calculations, and discussions as well as monitoring and evaluation stages to find out how much the partners' capabilities have increased. The achievement targets are in the output achievement table.